Pulmonary artery pseudoaneurysm in a young man with pulmonary hypertension on computed tomography angiography - Tairkhan B. Dautov; Bauyrzhan B. Kaliyev; Ruslan Y. Tukinov; Dinara S. Almenova; Zhanar Z. Kozhakhmetova; Nurmakhan Z. Zholshybek; Lyazzat A. Bastarbekova; Valeriy S. Ignatyev (Digital Diagnostics)
Pulmonary artery aneurysms and pseudoaneurysms are uncommon anomalies; however, their associated morbidity underscores the importance of recognizing them. Herein, we present a clinical case involving a 15-year-old male patient who presented at our clinic with complaints of hemoptysis. Upon diagnosis, a left lung aneurysm was found. Subsequent computed tomography angiography and intervention on the pulmonary arteries confirmed the presence of pulmonary artery aneurysms, elucidating that the hemoptysis was caused by the rupture of the aneurysm. The intervention on the pulmonary artery further confirmed the diagnosis. Early detection and management of pulmonary artery aneurysms are crucial, particularly in young patients, as timely intervention can prevent severe complications and improve patient outcomes. Raising awareness of these vascular abnormalities and promptly addressing them through appropriate diagnostic measures and interventions can help healthcare providers effectively mitigate the potential risks associated with pulmonary artery aneurysms, thereby enhancing patient care and prognosis.